'Run them dry': a retrospective experience with a restrictive fluid management strategy in severe imported falciparum malaria from a tertiary care university hospital in Berlin, Germany. (3rd March 2021) - Hoffmeister, Bodo; Aguilar Valdez, Abner D
Abstract: Background: Due to the unique pathophysiology with progressive mircocirculatory obstruction and simultaneously increased vascular permeability, overhydration can be rapidly harmful in patients with falciparum malaria. The outcome in all 558 cases hospitalised during 2001–2015 in the Charité University Hospital, Berlin, was favourable, independent of the antimalarial used. Here, the fluid management strategy in the most severely affected subgroup is examined. Methods: All fluids in 32 patients requiring treatment on intensive care units (ICUs) for >48 h were retrospectively quantified. All malaria-specific complications were followed up over the whole ICU stay. Results: Strong linear relationships between fluid intake and positive balances reflecting dehydration and increased vascular permeability were evident over the whole stay. With 2.2 (range: 0.7–6.9), 1.8 (0.6–6.1) and 1.3 (0.3–5.0) mL/kg/h on day 1, day 2 and over the remaining ICU stay, respectively, median fluid volumes remained below the actual WHO recommendations. No evidence for deterioration of any malaria-specific complication under such restrictive fluid management was found. The key prognostic parameter metabolic acidosis improved significantly over 48 h (p=0.02). All patients survived to discharge. Conclusions: These results suggest that in the face of markedly increased vascular permeability, a restrictive fluid management strategy is clinically safe in adults with severe imported falciparum malaria.